Prophylaxis of complications in venous surgery - Romano, R.; Leo, M.; Di Mitri, R. (Phlebologie, 2017)
Aim: The purpose of this article is to underline complications in venous surgery during the past 30 years and new ones arising with the introduction of technologies. We also discuss the “natural reduction” of some of these and how to prevent complications.Methods: We have analysed different types of studies on different surgical procedures in the treatment of varicose veins and compared them with own outcomes.Results: Considering all techniques, we have wound infections in 2,3–4 % of cases, cellulitis in 2,6–16 %, lymphatic complications in 1,3–60 %, pain in 2–23 %, neurologic disease including nerve damages, bruising and numbness in 0–50 %, thrombophlebitis in 0,3–20 %, deep vein thrombosis with or without pulmonary embolism in 0–5,7 %, injury of major vessel in 0,17 %, haematoma in 1,3–31 %, oedema in <1–15 %, hyperpigmentation in 3–11 %, ecchymosis in 0,8–9 %, skin burns in 0,2–8 %, erythema in 2–33 % and endothermal heat-induced-thrombosis (HEIT) in 0–7,5 % of cases.Conclusion: Our outcomes confirmed literature results. We conclude that new technologies improve results and reduce complications, as do tumescent anaesthesia, medical stockings, early mobilization and low weight heparin prophylaxis (LMWH) in high risk patients.
Keywords: Varicose vein surgery; prophylaxis in varicose vein surgery; postoperative complications